2012
DOI: 10.1186/1471-2334-12-97
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antiviral treatment and hospital admission delay on risk of death associated with 2009 A/H1N1 pandemic influenza in Mexico

Abstract: BackgroundIncreasing our understanding of the factors affecting the severity of the 2009 A/H1N1 influenza pandemic in different regions of the world could lead to improved clinical practice and mitigation strategies for future influenza pandemics. Even though a number of studies have shed light into the risk factors associated with severe outcomes of 2009 A/H1N1 influenza infections in different populations (e.g., [1-5]), analyses of the determinants of mortality risk spanning multiple pandemic waves and geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
2
21
0
3
Order By: Relevance
“…This result could be due to the small fraction of hospitalized patients that were treated with antivirals during the fall wave (∼9%) and the fact that decision to treat was not found to be related to symptoms severity [65]. We [65] recently reported a sharp drop in antiviral use from 50% in the spring and summer wave to 9% in the main fall pandemic in Mexico.…”
Section: Discussionmentioning
confidence: 98%
“…This result could be due to the small fraction of hospitalized patients that were treated with antivirals during the fall wave (∼9%) and the fact that decision to treat was not found to be related to symptoms severity [65]. We [65] recently reported a sharp drop in antiviral use from 50% in the spring and summer wave to 9% in the main fall pandemic in Mexico.…”
Section: Discussionmentioning
confidence: 98%
“…Three identified studies [110][111][112] were published versions of trials that were possibly unknown to us. We wrote to the first trial author to ask for CSRs, or equivalent, on 12 November 2013, and the author confirmed that the trials had not been completed.…”
Section: Electronic Searchesmentioning
confidence: 99%
“…Two RCTs were excluded from the meta-analysis because they were only synopsis reports 74,75 and another because it was not a full CSR. 76 We finally included 20 oseltamivir trials into stage 2: 11 on treatment in adults, 8,36,57,58,[60][61][62]66,67,69,[74][75][76][108][109][110][111][112] four in children 57,63,64 and five on prophylaxis: 51,61,65,68 two in adults, 51 two in the elderly 61,68 and one in households. 65 Of the 15 included treatment trials of oseltamivir, only three 8,36,63 were successful in recruiting the a priori planned sample size.…”
Section: Oseltamivirmentioning
confidence: 99%
“…These data could be relevant to improve vaccination coverage, and target groups not considered as high-risk subjects for complications of influenza infection. In Mexico, between April 1 through December 31, 2009, the mean case fatality ratio was 0.6% for those < 18 years, 2.8% for the group of 18-49 years and 8.5% for > 50 years [23].…”
Section: Discussionmentioning
confidence: 99%